Patient Perceptions of Telephone vs. In‐Person BRCA1/BRCA2 Genetic Counseling. Issue 3 (12th October 2015) - Peshkin, Beth N.; Kelly, Scott; Nusbaum, Rachel H.; Similuk, Morgan; DeMarco, Tiffani A.; Hooker, Gillian W.; Valdimarsdottir, Heiddis B.; Forman, Andrea D.; Joines, Jessica Rispoli; Davis, Claire; McCormick, Shelley R.; McKinnon, Wendy; et al.
Abstract: Telephone genetic counseling (TC) for hereditary breast/ovarian cancer risk has been associated with positive outcomes in high risk women. However, little is known about how patients perceive TC. As part of a randomized trial of TC versus usual care (UC; in‐person genetic counseling), we compared high risk women's perceptions of: (1) overall satisfaction with genetic counseling; (2) convenience; (3) attentiveness during the session; (4) counselor effectiveness in providing support; and (5) counselor ability to recognize emotional responses during the session. Among the 554 participants (TC, N  = 272; UC, N  = 282), delivery mode was not associated with self‐reported satisfaction. However, TC participants found counseling significantly more convenient than UC participants (OR = 4.78, 95 % CI = 3.32, 6.89) while also perceiving lower levels of support (OR = 0.56, 95 % CI = 0.40–0.80) and emotional recognition (OR = 0.53, 95 % CI = 0.37–0.76). In exploratory analyses, we found that non‐Hispanic white participants reported higher counselor support in UC than in TC (69.4 % vs. 52.8 %; OR = 3.06, 95 % CI = 1.39–6.74), while minority women perceived less support in UC vs. TC (58.3 % vs. 38.7 %; OR = 0.80, 95 % CI = 0.39–1.65). We discuss potential research and practice implications of these findings which may further improve the effectiveness and utilization of TC.